Giant Left Ventricular Aneurysm Following a Late Presentation STEMI in the COVID-19 Pandemic Era - Stougiannos, Pavlos; Malaxianaki, Eleftheria; Tolios, Panagiotis; Karvelas, George; Evdoridis, Constantinos; Tsiamis, Spyridon; Thomopoulos, Thomas; Dedeilias, Panagiotis; Trikas, Athanasios (Cardiology and Cardiovascular Medicine, 2021)
Left ventricular (LV) aneurysm is a serious mechanical complication following acute myocardial infarction (MI). Approximately 85% of true LV aneurysms are located at the apical and anteroseptal wall. They are associated with increased morbidity and mortality due to complications that can potentially occur, including heart failure, thromboembolism and tachyarrhythmias. As the need for prompt treatment is vital, transthoracic echocardiography, contrast echocardiography, computed tomography (CT) and cardiac magnetic resonance (CMR) are the preferred noninvasive modalities used for the diagnosis. The incidence of LV aneurysm as a complication of acute myocardial infarction has declined, primarily thanks to the advances in percutaneous coronary intervention and early revascularization. We report the case of a large LV apical aneurysm in a patient with a delayed presentation after ST-elevation myocardial infarction during the COVID-19 pandemic. A 60-year-old female with history of previous anterior myocardial infarction with delayed revascularization presented to the emergency department with worsening shortness of breath, orthopnea and marked limitation of physical activity. The transthoracic echocardiogram that was conducted revealed a giant LV aneurysm located at the apex as well as a markedly reduced left ventricular ejection fraction. Contrast echo-cardiography and cardiac CT were used to confirm these findings while CMR also provided accurate measurements of left ventricular volumes and mass. In addition, the extent of myocardial scar tissue and viability of the other regions of left ventricle were identified. The patient underwent a successful left ventricular reconstructive surgery leading to a significant functional status improvement.